If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 4g = -39 Solving -15 + 4g = -39 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 4g = -39 + 15 Combine like terms: -15 + 15 = 0 0 + 4g = -39 + 15 4g = -39 + 15 Combine like terms: -39 + 15 = -24 4g = -24 Divide each side by '4'. g = -6 Simplifying g = -6
| 16s^2-72s+81= | | 2x-23=835 | | 36w^2-49= | | 56=2x | | 25x^2-55x+30=0 | | 12h^2-17hj-5j^2= | | 2y-9=13 | | x-361-195+1236-22=599 | | 3x+5=x-5 | | 5v^2+21v-20= | | -72=-5(n+6)-7 | | x-152+419=794 | | 20v^3+105v^2-100v= | | 6x=8+7x | | 20=4(x+7) | | 4y+8=16 | | 3x-2x+8-10=7 | | 10+x=28 | | -4x-4+x-2y+7x= | | 2=3(x+7)+2 | | 4-(7n-5)+18n=5(5n+1) | | 25=-3k+5(k+7) | | 2x+3=19+5x | | x^2-0.3=-0.06x | | 9(2a-3)-5(3a-2)=-a+9(a-8) | | 5d-17-3d+18=15d+17-11d | | -8-4(2q-3)=-16 | | 7=-5(5+7n)-3 | | 7n-1=3k-5 | | -8(1+8a)=-8 | | 4x^2+18x+20=0 | | -(-7+1)=-(-3-8q) |